Final answer:
The equation of the new function, after shifting the linear parent function f(x) = x up 6 units, is g(x) = x + 6.
Step-by-step explanation:
The equation of the new function, after shifting the linear parent function f(x) = x up 6 units, is g(x) = x + 6.
To obtain the new function, we add 6 to the original function. This means that for any value of x, the corresponding value of g(x) is obtained by taking the value of f(x) and adding 6 to it.
For example, if x = 3, the original function gives us f(3) = 3, and the new function gives us g(3) = 3 + 6 = 9.